Fatores que favorecem o desenvolvimento de microalgas planctônicas em sistemas de arroz irrigado pré-germinado, no Sul do Brasil - Ravasa, Tiziane Horbach (Universidade do Vale do Rio dos Sinos, 2013)
In various countries rice planting is the most important activity, therefore being the main source of food for half the world’s population. In rice fields with a pre-germinated planting system the permanent water may be favorable to the developing of various groups of organisms, as in phytoplankton communities. Thus, the following paper has the objective to evaluate the factors that affect the development of phytoplankton biomass irrigated pre-germinated rice fields as well as evaluate how the sources of irrigation can contribute to the establishment of blooming and its effects over the phytoplankton richness and diversity in pre-germinated rice systems. In order to accomplish this, water samples were collected for biological analysis (phytoplankton density, richness and diversity) in the area preparation right after the planting and in six other occasions during the planting cycle, in three fields situated in the county of Viamão/RS. It is expected, with this study, that the information obtained may contribute with specialized knowledge in view of mitigating the impacts of algae development in these systems, understanding of the process determining planktonic algae in the environment under study, and understand the role of sources in determining blooming and its effect over the diversity of the phytoplankton community pre-germinated irrigated rice fields.
Keywords: Arroz irrigado; Fitoplâncton; Florações; Irrigated rice; Phytoplankton; Blooming; ACCNPQ::Ciências Biológicas::Biologia Geral